1998
DOI: 10.1165/ajrcmb.19.5.3072
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Chlamydia pneumoniae and Human Alveolar Macrophages: Infection and Inflammatory Response

Abstract: The obligate intracellular pathogen Chlamydia pneumoniae is associated with chronic respiratory, atherosclerotic, and rheumatic disease. The alveolar macrophage (AM) is a potential target cell for the pathogen and may contribute to respiratory immunopathology. We therefore investigated in vitro the interaction between chlamydiae and macrophages with cocultures of C. pneumoniae and AM from 12 healthy volunteers. Inflammatory responses were evaluated through lucigenin-amplified chemiluminescence; secretion of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 29 publications
5
85
0
1
Order By: Relevance
“…In acute exacerbation of COPD, the pulmonary compartment represents a site of localised inflammation, in which AMs play a pivotal role in the host defence against bacterial pathogens [16]. Initially, C. pneumoniae infects AMs, which results in enhanced secretion of the pro-inflammatory cytokines IL-1b and TNF-a [17]. Besides the beneficial effects of proinflammatory cytokine secretion in infectious diseases, some of their biological activities may contribute to structural tissue damage if an adequate anti-inflammatory immune response is lacking [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In acute exacerbation of COPD, the pulmonary compartment represents a site of localised inflammation, in which AMs play a pivotal role in the host defence against bacterial pathogens [16]. Initially, C. pneumoniae infects AMs, which results in enhanced secretion of the pro-inflammatory cytokines IL-1b and TNF-a [17]. Besides the beneficial effects of proinflammatory cytokine secretion in infectious diseases, some of their biological activities may contribute to structural tissue damage if an adequate anti-inflammatory immune response is lacking [18].…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokine secretion pattern of C. pneumoniae-infected AMs and PBMCs from healthy persons has been described previously [17,19], whereas data concerning the release of anti-inflammatory cytokines are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Since smoking is a very strong risk factor for lung cancer, any interpretation of the C. pneumoniae-lung cancer relationship in a smoking population should consider the possibility of residual confounding effect even after adjustment using standard statistical techniques. On the other hand, in vitro studies demonstrate that infection with C. pneumoniae readily induces production of reactive oxygen species, TNF-␣, IL-1␤ and IL-8 in alveolar macrophages, 11 thus supporting its potential to act as an inflammatory stimulus and promote lung carcinogenesis. It is possible that chronic C. pneumoniae infection may act synergistically with carcinogens present in cigarette smoke to initiate or promote carcinogenesis, such that the effect is only evident in smokers.…”
Section: Dear Sirmentioning
confidence: 99%
“…These studies demonstrated that immune-stimulating adjuvants like aluminum hydroxide (alum) are frequently required to elicit appropriate in vivo adaptive immunity. They also demonstrated that many of these adjuvants mediate their effects via activating innate immunity Toll-like receptors (TLRs) and NODs and inducing the production of proinflammatory cytokines (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This can readily be appreciated in studies highlighting the important role(s) that TLRs plays in the pathogenesis of asthma-like Th2 adaptive immune responses (18) and studies that demonstrate that TLR-2 ligands such as Pam-3-cys are potent Th2 adjuvants in vivo (19,20).…”
mentioning
confidence: 99%